Microloan approval and its impact on SMEs performance in Malaysia - Wen, Tan Pei; Mohd Ashhari, Zariyawati; Faizal, Diana Rose; Mokhtar, Suraya Hanim (American Scientific Publishers, 2018)
There is no doubt that small and medium-sized enterprises (SMEs) are important to countries worldwide. SMEs’ contributions in recent years have dramatically and continuously increased various nations’ gross domestic products. Therefore, the growth of SMEs is forecast to continue to grow yearly. With sufficient finance, the development of SMEs is believed to grow considerably, and consequently boost Malaysia’s economy. In addition to acquiring funds from relatives, SMEs have the opportunity to obtain microloans from microfinance institutions to establish or increase their capital, which further helps them to expand their business. Therefore, the aim of this study is to examine whether SMEs’ characteristics influence microloan approval and the impact that microloan has on business performance of SMEs. Results from primary data show that microloan approval is influenced by SMEs characteristics and microloans do have an impact on SMEs’ performance. We suggest that loan approval to SMEs can improve business performance, especially together with the existence of business support such as technical training and management training.